A kind of heat insulation material and preparation method thereof
Through the disassembled structure of high-strength glass fiber cloth, carbon nanotube membrane, aerogel felt and basalt cloth layer, combined with aramid-clad steel wire fixed connection and liquid silicone spraying technology, the problem of insufficient insulation performance of existing thermal insulation materials in high temperature environments is solved, and high-efficiency thermal insulation, fire resistance and flame retardant performance are achieved.
Patent Information
- Application Number
- CN202410927330.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-07-11
AI Technical Summary
The existing thermal insulation materials lack thermal insulation performance in high temperature environments, and the material density is high and not easy to follow, which poses environmental protection and safety hazards.
The split-layer structure of high-strength glass fiber cloth, carbon nanotube film, aerogel felt and basalt cloth layer is fixedly connected by aramid-clad steel wire, and liquid silicone is sprayed to enhance thermal insulation performance.
It achieves effective heat insulation in a high temperature environment of 350℃, with the cold surface temperature not higher than 90℃, the product has low apparent density, low thermal conductivity, low water absorption, and has the characteristics of fire resistance, flame retardant and low powder loss.
Smart Images

Figure CN118744585B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal protection, and in particular relates to a thermal insulation material and a preparation method thereof. Background Art
[0002] With the advancement of engine technology, the temperature between turbines has increased from 950℃ to 1050℃, and the heat radiation of the engine and tail nozzle has also increased. The requirements for engine compartment and structural design have also undergone qualitative changes, which are mainly reflected in the engine combustion chamber (750℃), engine tail nozzle (350-450℃), and the inner surface of the engine fairing (300℃). Thermal insulation materials mainly include asbestos thermal insulation materials, ceramic fibers, silicon aerogel composites, silicon foam composites, etc. At present, ceramic rigid thermal insulation materials and flexible thermal insulation felts have been successfully applied to aircraft thermal protection. The characteristics of asbestos thermal insulation materials are high specific gravity (340Kg / m 3 ), not easy to shape, not environmentally friendly, carcinogenic; the characteristics of ceramic fiber are high specific gravity (1000Kg / m 3 ), not easy to follow the shape, easy to break; the characteristics of silicon aerogel composite materials are poor tensile strength, easy to puncture, and poor fire resistance; the characteristics of silicon foam composite materials are poor thermal insulation (cannot withstand 300℃ for a long time) and thickness limit (<15mm). Summary of the invention
[0003] The problem to be solved by the present invention is to reduce the specific gravity of the material and improve the thermal insulation performance of the material, and a thermal insulation material and a preparation method thereof are provided.
[0004] To achieve the above object, the present invention is implemented through the following technical solutions:
[0005] A method for preparing a thermal insulation material comprises the following steps:
[0006] S1. Take a piece of high-strength glass fiber cloth and a piece of carbon nanotube film of the same length and width and set aside;
[0007] S2. Take 2 pieces of aerogel felt, the length of the aerogel felt is 20-40 mm less than the length of the high-strength glass fiber cloth in step S1, the width of the aerogel felt is the same as the width of the high-strength glass fiber cloth in step S1, and the thickness of the aerogel felt is in the range of 3-4 mm for standby use;
[0008] S3. stacking two aerogel felts together, and then placing a carbon nanotube film on the bottom surface of the second aerogel felt, and then placing a high-strength glass fiber cloth, and lap the two ends of the carbon nanotube film and the high-strength glass fiber cloth to the top surface of the first aerogel felt in reverse, and then placing a basalt cloth with a silicone coating to completely cover the top surface;
[0009] S4. Aramid coated steel wire is used as the sewing wire material of the thermal insulation material at both ends of the overlap, and the sewing method uses high-strength glass fiber cloth for edging, and double-thread sewing according to the edge of the basalt cloth with silicone coating;
[0010] S5. After sewing is completed, liquid silicone is sprayed on the stitch position in the fiber direction of the basalt cloth to obtain the thermal insulation material.
[0011] Furthermore, the surface density of the high-strength glass fiber cloth is 95-115 g / m 2 The surface density of the high-strength glass fiber cloth is 95-115g / m 2 The surface density of the carbon nanotube film is 10 g / m 2 , thickness is 15 μm, the heat resistance temperature of the carbon nanotube film is 500°C, and the material density of the aerogel felt is 0.2-0.3 mg / cm 3 The thermal conductivity is 0.012-0.016 W / (m·K). The aerogel felt is prepared by compounding an inorganic reinforcing material with a sol by a sol-gel method and drying the compound to form a nanoporous inorganic silicon aerogel felt.
[0012] Furthermore, the surface density of the basalt cloth is 670-810 g / m 2 , the temperature resistance is -55℃-260℃, the density of the silicone coating on the basalt cloth is 70g / ㎡, and the temperature resistance of the silicone coating is 160℃.
[0013] Furthermore, the diameter of the aramid-coated steel wire is 0.28 mm, the temperature resistance at the center is 800° C., and the breaking strength is 100-200N.
[0014] A thermal insulation material is realized by relying on the preparation method of the thermal insulation material, the thermal insulation material comprises a high-strength glass fiber cloth layer, a carbon nanotube film, two aerogel felt layers, and a basalt cloth layer, the glass fiber cloth layer, the carbon nanotube film, the two aerogel felt layers, and the basalt cloth layer are arranged in sequence from bottom to top, the glass fiber cloth layer and the carbon nanotube film wrap the end faces of the two aerogel felt layers, and the high-strength glass fiber cloth layer, the carbon nanotube film, the two aerogel felt layers, and the basalt cloth layer are fixedly connected by aramid-coated steel wires.
[0015] A method for preparing a thermal insulation material comprises the following steps:
[0016] S1. Take a piece of high-strength glass fiber cloth and a piece of carbon nanotube film of the same length and width and set aside;
[0017] S2. Take 2 pieces of aerogel felt, the first piece of aerogel felt is 18.84-25.12 mm longer than the second piece of aerogel felt, the length of the first piece of aerogel felt is 80-100 mm less than the length of the high-strength glass fiber cloth in step S1, the width of the two pieces of aerogel felt is the same as the width of the high-strength glass fiber cloth in step S1, and the thickness of the aerogel felt is in the range of 3-4 mm, and is ready for use;
[0018] S3. Stack two aerogel felts in staggered layers, and then place a carbon nanotube film on the bottom surface of the second aerogel felt, and then place a high-strength glass fiber cloth, and overlap the two ends of the carbon nanotube film and the high-strength glass fiber cloth in reverse to the top surface of the first aerogel felt, and then place a basalt cloth with a silicone coating to completely cover the top surface;
[0019] S4. Aramid coated steel wire is used as the sewing wire material of the thermal insulation material at both ends of the overlap, and the sewing method uses high-strength glass fiber cloth to wrap the edge, and double-thread sewing is carried out along the edge of the basalt cloth with silicone coating, and then heat-insulating flame-retardant Velcro is sewn on the upper and lower surfaces of both ends of the basalt cloth;
[0020] S5. After sewing is completed, liquid silicone is sprayed on the pin position in the fiber direction of the basalt cloth to obtain a thermal insulation material;
[0021] S6. Then wrap the high-strength glass fiber cloth surface of the thermal insulation material tightly against the tubular product, and after wrapping, use thermal insulation and flame-retardant Velcro for bonding.
[0022] Furthermore, the surface density of the high-strength glass fiber cloth is 95-115 g / m 2 The surface density of the carbon nanotube film is 10 g / m 2 , thickness is 15 μm, the heat resistance temperature of the carbon nanotube film is 500°C, and the material density of the aerogel felt is 0.2-0.3 mg / cm 3 The thermal conductivity is 0.012-0.016 W / (m·K). The aerogel felt is prepared by compounding an inorganic reinforcing material with a sol by a sol-gel method and drying the compound to form a nanoporous inorganic silicon aerogel felt.
[0023] Furthermore, the surface density of the basalt cloth is 670-810 g / m 2 , the temperature resistance is -55℃-260℃, the density of the silicone coating on the basalt cloth is 70g / ㎡, and the temperature resistance of the silicone coating is 160℃.
[0024] Furthermore, the diameter of the aramid-coated steel wire is 0.28 mm, the temperature resistance at the center is 800° C., and the breaking strength is 100-200N.
[0025] A heat-insulating material is realized by relying on the preparation method of the heat-insulating material, the heat-insulating material comprises a high-strength glass fiber cloth layer, a carbon nanotube film, two aerogel felt layers, and a basalt cloth layer, the glass fiber cloth layer, the carbon nanotube film, the two aerogel felt layers, and the basalt cloth layer are arranged in staggered layers from bottom to top, the glass fiber cloth layer and the carbon nanotube film wrap the end faces of the two aerogel felt layers, the upper left partial area and the lower right partial area of the basalt cloth layer are pasted with heat-insulating flame-retardant Velcro, the high-strength glass fiber cloth layer, the carbon nanotube film, the two aerogel felt layers, and the basalt cloth layer are fixedly connected by aramid-coated steel wires, and then wrapped on a tubular product and pasted with two heat-insulating flame-retardant Velcros.
[0026] Beneficial effects of the present invention:
[0027] The heat-insulating material of the present invention has the advantages that the working conditions are that the hot surface temperature is 350°C, the cold surface temperature is not higher than 90°C, the thickness is 7±1mm, and the apparent density of the product is about 0.25g / cm 3 The thermal conductivity is 0.023W / (m·K), the water absorption is 2.5%, and it has a flame temperature of 1100℃±80℃, a heat flux of 116±10kw / ㎡, and can continue to ablate for 15 minutes without being burned through.
[0028] The heat-insulating material described in the present invention has the characteristics of resistance to low temperature, resistance to moisture and heat, resistance to media, resistance to mildew and the like.
[0029] The preparation method of a heat-insulating material described in the present invention can be designed according to the structure of the product, and flame-retardant Velcro is used for bonding and fixing, which can achieve rapid installation and disassembly, and has the conditions for replacement by an external factory in airborne products. In order to solve the problem of powder shedding of aerogel felt during use, the present invention uses a heat-insulating carbon nanotube film as the wrapping material for the hot surface, and the cold surface is wrapped with basalt cloth with a silicone coating, which can effectively inhibit the leakage of silica powder from the gaps between the woven fibers while ensuring the overall product structural strength.
[0030] The thermal insulation material described in the present invention ensures the reliability of the material in a high-temperature environment for a long time. Therefore, the hot surface fiber material is made of high-strength glass fiber cloth, the fiber weaving density of which is relatively small, and the fiber cloth itself has pores, so silicon dioxide powder will seep out when it is in direct contact with the inorganic silicone aerogel felt. Therefore, a carbon nanotube film that can withstand a temperature of 500°C is used to wrap the high-strength glass fiber cloth and the inorganic silicone aerogel felt.
[0031] The preparation method of the heat insulation material described in the present invention can achieve the effect of heat insulation temperature of 90-350°C by using inorganic silicon aerogel, and replace the hydroxyl groups on the surface of the gel with hydrophobic organic groups to achieve the hydrophobic and oleophobic functions of the aerogel felt. The fiber felt is etched on the surface with an acid solution to improve the bonding force between the silicon dioxide powder and the substrate, thereby achieving the function of low powder loss rate.
[0032] The heat insulation material described in the present invention has the condition of being replaced by an external factory in an airborne product.
[0033] The heat insulation material of the present invention is used for wrapping tubular products to prevent the butt joint of the interface heat insulation material from resulting in no heat insulation layer in the butt joint area and heat insulation failure. The heat insulation material selects two layers for staggered overlap to ensure the heat insulation medium at the interface position. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic structural diagram of a heat-insulating material according to the present invention;
[0035] Figure 2 It is a schematic structural diagram of a heat-insulating material used for tubular products of the present invention;
[0036] Figure 3 This is a real photo of the thermal insulation material used for tubular products of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the specific embodiments described are only part of the embodiments of the present invention, rather than all of the specific embodiments. The components of the specific embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations, and the present invention can also have other embodiments.
[0038] Therefore, the following detailed description of the specific embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected specific embodiments of the present invention. Based on the specific embodiments of the present invention, all other specific embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0039] In order to further understand the content, features and effects of the present invention, the following specific implementation methods are given as examples, and the attached Figure 1 -Attached Figure 3 The detailed instructions are as follows:
[0040] Embodiment 1:
[0041] A method for preparing a thermal insulation material comprises the following steps:
[0042] S1. Take a piece of high-strength glass fiber cloth and a piece of carbon nanotube film of the same length and width and set aside;
[0043] S2. Take 2 pieces of aerogel felt, the length of the aerogel felt is 20-40 mm less than the length of the high-strength glass fiber cloth in step S1, the width of the aerogel felt is the same as the width of the high-strength glass fiber cloth in step S1, and the thickness of the aerogel felt is in the range of 3-4 mm for standby use;
[0044] S3. stacking two aerogel felts together, and then placing a carbon nanotube film on the bottom surface of the second aerogel felt, and then placing a high-strength glass fiber cloth, and lap the two ends of the carbon nanotube film and the high-strength glass fiber cloth to the top surface of the first aerogel felt in reverse, and then placing a basalt cloth with a silicone coating to completely cover the top surface;
[0045] S4. Aramid coated steel wire is used as the sewing wire material of the thermal insulation material at both ends of the overlap, and the sewing method uses high-strength glass fiber cloth for edging, and double-thread sewing according to the edge of the basalt cloth with silicone coating;
[0046] S5. After sewing is completed, liquid silicone is sprayed on the stitch position in the fiber direction of the basalt cloth to obtain the thermal insulation material.
[0047] Furthermore, the surface density of the high-strength glass fiber cloth is 95-115 g / m 2 The surface density of the carbon nanotube film is 10 g / m 2 , thickness is 15 μm, the heat resistance temperature of the carbon nanotube film is 500°C, and the material density of the aerogel felt is 0.2-0.3 mg / cm 3 The thermal conductivity is 0.012-0.016 W / (m·K). The aerogel felt is prepared by compounding an inorganic reinforcing material with a sol by a sol-gel method and drying the compound to form a nanoporous inorganic silicon aerogel felt.
[0048] Furthermore, the surface density of the basalt cloth is 670-810 g / m 2 , the temperature resistance is -55℃-260℃, the density of the silicone coating on the basalt cloth is 70g / ㎡, and the temperature resistance of the silicone coating is 160℃.
[0049] Furthermore, the diameter of the aramid-coated steel wire is 0.28 mm, the temperature resistance at the center is 800° C., and the breaking strength is 100-200N.
[0050] Furthermore, high-strength glass fiber cloth can withstand long-term heat temperatures of less than 700°C;
[0051] Furthermore, the carbon nanotube film has excellent physical and chemical properties, can withstand temperatures of 2000°C under vacuum or inert gas conditions and temperatures below 500°C under air conditions, and has good antioxidant capacity.
[0052] Furthermore, the aerogel felt is made by compounding the inorganic reinforcing material with the sol through the sol-gel method, and then drying it to make a nanoporous inorganic silicon aerogel felt. The resilience and "powder loss" of silicon-based aerogel can be improved by combining organic polymers with silane molecules or introducing organic functional groups with low surface energy. Different inorganic reinforcing fibers are introduced to adapt to different temperature-resistant working conditions. The nanopore structure, thickness and skeleton structure of the inorganic silicon aerogel have a great influence on the thermal insulation performance. The surface of the inorganic silicon aerogel is modified by replacing the hydroxyl groups on the surface of the gel with hydrophobic organic groups to form a hydrophobic inorganic silicon aerogel, which can be used in a humid environment to maintain the structure and thermal insulation effect of the aerogel.
[0053] 1. Use a specific hydrophobic modifier to replace the hydrophilic silanol groups on the inorganic silica aerogel with hydrophobic non-polar groups, thereby enhancing the hydrophobicity of the gel (water absorption rate is about 1.5%);
[0054] 2. Use acid solution to etch the surface of the fiber felt to activate the surface of the felt, improve the adhesion with silicon dioxide and reduce the generation of dust.
[0055] The pore size distribution of the structure is 1-100nm, with high porosity (80%-99%), high specific surface area (1000m 2 / g), ultra-low density (1-200mg / cm 3 ), low thermal conductivity 0.012 ~ 0.016W / (m·K).
[0056] Furthermore, the basalt cloth material is dense and impermeable, can completely block the aerogel from falling off, has a certain strength, good process adaptability, and can be sewn and composited with other flexible materials.
[0057] Furthermore, since the aramid coated steel wire will pass through the insulation material as a whole during the sewing process, there is a possibility of powder falling at the pinhole position during use. Therefore, liquid silicone is diluted with a special solvent and sprayed onto the cold surface of the aerogel insulation pad. The silicone molecular layer covers the insulation pad and cross-links into a dense film to prevent powder falling at the pinhole position.
[0058] Furthermore, a method for preparing a thermal insulation material comprises a high-strength glass fiber cloth layer 1, a carbon nanotube film 2, two aerogel felt layers 3, and a basalt cloth layer 4, wherein the glass fiber cloth layer 1, the carbon nanotube film 2, the two aerogel felt layers 3, and the basalt cloth layer 4 are arranged in sequence from bottom to top, and the glass fiber cloth layer 1 and the carbon nanotube film 2 wrap the end surfaces of the two aerogel felt layers 3, and the high-strength glass fiber cloth layer 1, the carbon nanotube film 2, the two aerogel felt layers 3, and the basalt cloth layer 4 are fixedly connected by an aramid-coated steel wire 5, such as Figure 1 shown.
[0059] Furthermore, the performance test of the thermal insulation material is shown in Table 1:
[0060] Table 1:
[0061]
[0062]
[0063] Embodiment 2:
[0064] A method for preparing a thermal insulation material comprises the following steps:
[0065] S1. Take a piece of high-strength glass fiber cloth and a piece of carbon nanotube film of the same length and width and set aside;
[0066] S2. Take 2 pieces of aerogel felt, the length of the aerogel felt is 20-40 mm less than the length of the high-strength glass fiber cloth in step S1, the width of the aerogel felt is the same as the width of the high-strength glass fiber cloth in step S1, and the thickness of the aerogel felt is in the range of 3-4 mm for standby use;
[0067] S3. Stack two aerogel felts in staggered layers, and then place a carbon nanotube film on the bottom surface of the second aerogel felt, and then place a high-strength glass fiber cloth, and overlap the two ends of the carbon nanotube film and the high-strength glass fiber cloth in reverse to the top surface of the first aerogel felt, and then place a basalt cloth with a silicone coating to completely cover the top surface;
[0068] S4. Aramid coated steel wire is used as the sewing wire material of the thermal insulation material at both ends of the overlap, and the sewing method uses high-strength glass fiber cloth to wrap the edge, and double-thread sewing is carried out along the edge of the basalt cloth with silicone coating, and then heat-insulating flame-retardant Velcro is sewn on the upper and lower surfaces of both ends of the basalt cloth;
[0069] S5. After sewing is completed, liquid silicone is sprayed on the pin position in the fiber direction of the basalt cloth to obtain a thermal insulation material;
[0070] S6. Then wrap the high-strength glass fiber cloth surface of the thermal insulation material tightly against the tubular product, and after wrapping, use thermal insulation and flame-retardant Velcro for bonding.
[0071] Furthermore, the surface density of the high-strength glass fiber cloth is 95-115 g / m 2 The surface density of the carbon nanotube film is 10 g / m 2 , thickness is 15 μm, the heat resistance temperature of the carbon nanotube film is 500°C, and the material density of the aerogel felt is 0.2-0.3 mg / cm 3 The thermal conductivity is 0.012-0.016 W / (m·K). The aerogel felt is prepared by compounding an inorganic reinforcing material with a sol by a sol-gel method and drying the compound to form a nanoporous inorganic silicon aerogel felt.
[0072] Furthermore, the surface density of the basalt cloth is 670-810 g / m 2 , the temperature resistance is -55℃-260℃, the density of the silicone coating on the basalt cloth is 70g / ㎡, and the temperature resistance of the silicone coating is 160℃.
[0073] Furthermore, the diameter of the aramid-coated steel wire is 0.28 mm, the temperature resistance at the center is 800° C., and the breaking strength is 100-200N.
[0074] Furthermore, high-strength glass fiber cloth can withstand long-term heat temperatures of less than 700°C;
[0075] Furthermore, the carbon nanotube film has excellent physical and chemical properties, can withstand temperatures of 2000°C under vacuum or inert gas conditions and temperatures below 500°C under air conditions, and has good antioxidant capacity.
[0076] Furthermore, the aerogel felt is made by compounding the inorganic reinforcing material with the sol through the sol-gel method, and then drying it to make a nanoporous inorganic silicon aerogel felt. The resilience and "powder loss" of silicon-based aerogel can be improved by combining organic polymers with silane molecules or introducing organic functional groups with low surface energy. Different inorganic reinforcing fibers are introduced to adapt to different temperature-resistant working conditions. The nanopore structure, thickness and skeleton structure of the inorganic silicon aerogel have a great influence on the thermal insulation performance. The surface of the inorganic silicon aerogel is modified by replacing the hydroxyl groups on the surface of the gel with hydrophobic organic groups to form a hydrophobic inorganic silicon aerogel, which can be used in a humid environment to maintain the structure and thermal insulation effect of the aerogel.
[0077] 1. Use a specific hydrophobic modifier to replace the hydrophilic silanol groups on the inorganic silica aerogel with hydrophobic non-polar groups, thereby enhancing the hydrophobicity of the gel (water absorption rate is about 1.5%);
[0078] 2. Use acid solution to etch the surface of the fiber felt to activate the surface of the felt, improve the adhesion with silicon dioxide and reduce the generation of dust.
[0079] The pore size distribution of the structure is 1-100nm, with high porosity (80%-99%), high specific surface area (1000m 2 / g), ultra-low density (1-200mg / cm 3 ), low thermal conductivity 0.012 ~ 0.016W / (m·K).
[0080] Furthermore, the basalt cloth material is dense and impermeable, can completely block the aerogel from falling off, has a certain strength, good process adaptability, and can be sewn and composited with other flexible materials.
[0081] Furthermore, since the aramid coated steel wire will pass through the insulation material as a whole during the sewing process, there is a possibility of powder falling at the pinhole position during use. Therefore, liquid silicone is diluted with a special solvent and sprayed onto the cold surface of the aerogel insulation pad. The silicone molecular layer covers the insulation pad and cross-links into a dense film to prevent powder falling at the pinhole position.
[0082] Furthermore, the method for preparing a thermal insulation material comprises a high-strength glass fiber cloth layer 1, a carbon nanotube film 2, two aerogel felt layers 3, and a basalt cloth layer 4, wherein the glass fiber cloth layer 1, the carbon nanotube film 2, the two aerogel felt layers 3, and the basalt cloth layer 4 are arranged in staggered layers from bottom to top, the glass fiber cloth layer 1 and the carbon nanotube film 2 wrap the end faces of the two aerogel felt layers 3, and the upper left local area and the lower right local area of the basalt cloth layer 4 are pasted with a thermal insulation and flame retardant Velcro 6, the high-strength glass fiber cloth layer 1, the carbon nanotube film 2, the two aerogel felt layers 3, and the basalt cloth layer 4 are fixedly connected by an aramid coated steel wire 5, and then wrapped on a tubular product, and pasted with two thermal insulation and flame retardant Velcro 6, such as Figure 2 As shown, the actual photos are as Figure 3 shown.
[0083] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0084] Although the present application has been described above with reference to specific embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, as long as there is no structural conflict, the various features in the specific embodiments disclosed in the present application may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a thermal insulation material, characterized in that: The steps include: S1. Take a piece of high-strength glass fiber cloth and a piece of carbon nanotube film of the same length and width and set aside; S2. Take 2 pieces of aerogel felt, the first piece of aerogel felt is 18.84-25.12mm longer than the second piece of aerogel felt, the length of the first piece of aerogel felt is less than the length of the high-strength glass fiber cloth in step S1 80-100mm, the width of the 2 pieces of aerogel felt is the same as the width of the high-strength glass fiber cloth in step S1, the thickness of the aerogel felt is in the range of 3-4mm, and set aside; S3. Stack two aerogel felts in staggered layers, and then place a carbon nanotube film on the bottom surface of the second aerogel felt, and then place a high-strength glass fiber cloth, and overlap the two ends of the carbon nanotube film and the high-strength glass fiber cloth in reverse to the top surface of the first aerogel felt, and then place a basalt cloth with a silicone coating to completely cover the top surface; S4. Aramid-coated steel wire is used as the sewing wire of the insulation material at both ends of the overlap, and the sewing method uses high-strength glass fiber cloth to wrap the edges, and then high-temperature resistant and flame-retardant Velcro is sewn on the upper and lower surfaces of both ends of the basalt cloth; S5. After sewing is completed, liquid silicone is sprayed on the pin position of the basalt cloth to obtain a thermal insulation material; S6. Then wrap the high-strength glass fiber cloth of a heat-insulating material close to the tubular product, and after wrapping, use high-temperature resistant flame-retardant Velcro for bonding; The surface density of the high-strength glass fiber cloth is 95-115g / m 2 The surface density of the carbon nanotube film is 10 g / m 2 , thickness is 15 μm, the heat resistance temperature of the carbon nanotube film is 500°C, and the material density of the aerogel felt is 0.2-0.3 mg / cm 3 , the thermal conductivity is 0.012-0.016 W / (m•K), the aerogel felt is prepared by compounding an inorganic reinforcing material with a sol by a sol-gel method, and drying the compound to form a nanoporous inorganic silicon aerogel felt; The surface density of the basalt cloth is 670-810g / m 2 , the temperature resistance is -55℃-260℃, the density of the silicone coating on the basalt cloth is 70g / ㎡, and the temperature resistance of the silicone coating is 160℃; The diameter of the aramid-coated steel wire is 0.28 mm, and the temperature resistance at the center is 800°C; Using a hydrophobic modifier, the hydrophilic silanol groups on the inorganic silica aerogel are replaced with hydrophobic non-polar groups, thereby enhancing the hydrophobicity of the gel; The fiber felt is etched with an acid solution to activate the surface of the felt, improve adhesion with silicon dioxide and reduce dust generation.
2. A thermal insulation material, implemented according to the method for preparing a thermal insulation material according to claim 1, characterized in that: The thermal insulation material comprises a high-strength glass fiber cloth layer (1), a carbon nanotube film (2), two aerogel felt layers (3), and a basalt cloth layer (4); the glass fiber cloth layer (1), the carbon nanotube film (2), the two aerogel felt layers (3), and the basalt cloth layer (4) are arranged in staggered layers from bottom to top; the glass fiber cloth layer (1) and the carbon nanotube film (2) wrap the end faces of the two aerogel felt layers (3); high-temperature resistant flame-retardant Velcro (6) is adhered to the upper left partial area and the lower right partial area of the basalt cloth layer (4); the high-strength glass fiber cloth layer (1), the carbon nanotube film (2), the two aerogel felt layers (3), and the basalt cloth layer (4) are fixedly connected by an aramid-coated steel wire (5), and then wrapped on a tube-shaped product and adhered by using two high-temperature resistant flame-retardant Velcro (6).
Citation Information
Patent Citations
Basalt fiber silica gel coating cloth and preparation method thereof
CN117626649A
Aramid fiber wrapped steel wire high-temperature-resistant sewing thread
CN216765169U
Heat insulation structure
CN219313011U
Flexible heat preservation sleeve for pipeline
CN220453103U